2019
DOI: 10.1371/journal.pone.0216438
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and highly sensitive detection of pyocyanin biomarker in different Pseudomonas aeruginosa infections using gold nanoparticles modified sensor

Abstract: Successful antibiotic treatment of infections relies on accurate and rapid identification of the infectious agents. Pseudomonas aeruginosa is implicated in a wide range of human infections that mostly become complicated and life threating, especially in immunocompromised and critically ill patients. Conventional microbiological methods take more than three days to obtain accurate results. Pyocyanin is a distinctive electroactive biomarker for Pseudomonas aeruginosa … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 48 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…However, those methods are time-consuming as they require the target molecules/proteins to be purified from bacterial cultures. Recently, nanoparticles have been developed to allow rapid identification of pyocyanin [ 131 ] and LasA protease [ 132 ] with high sensitivity even in the presence of other species within cell cultures. Gold nanoparticles (Au NPs) deposited onto indium tin oxide electrodes was able to enhance the detection of pyocyanin at a concentration as low as 40 µM as compared to the minimum 80 µM of pyocyanin detected using unmodified electrodes [ 131 ].…”
Section: Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, those methods are time-consuming as they require the target molecules/proteins to be purified from bacterial cultures. Recently, nanoparticles have been developed to allow rapid identification of pyocyanin [ 131 ] and LasA protease [ 132 ] with high sensitivity even in the presence of other species within cell cultures. Gold nanoparticles (Au NPs) deposited onto indium tin oxide electrodes was able to enhance the detection of pyocyanin at a concentration as low as 40 µM as compared to the minimum 80 µM of pyocyanin detected using unmodified electrodes [ 131 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Recently, nanoparticles have been developed to allow rapid identification of pyocyanin [ 131 ] and LasA protease [ 132 ] with high sensitivity even in the presence of other species within cell cultures. Gold nanoparticles (Au NPs) deposited onto indium tin oxide electrodes was able to enhance the detection of pyocyanin at a concentration as low as 40 µM as compared to the minimum 80 µM of pyocyanin detected using unmodified electrodes [ 131 ]. Encapsulating the Au NPs with a thin layer of polyaniline hydrochloride (PANI) forming PANI/Au core-shell NPs increased the sensitivity of the PANI/Au NPs-modified electrodes towards pyocyanin down to 36 µM, which could accelerate the diagnostic process, achieving effective treatments and prevention of chronic infections [ 131 ].…”
Section: Diagnosticsmentioning
confidence: 99%
“…Elkhawaga et al have prepared PANI/Au NPs/ITO electrode as PYO sensor in a culture of P. aeruginosa. The results indicated that PANI/Au NPs/ ITO electrode is more sensitive toward PYO biomarker than either bare ITO electrode or Au NPs/ITO electrode with LOD of 500 nM [42]. The enhancement of the electrochemical activity of PANI/Au NPs/ITO modified electrode towards the PYO related to the presence of positive charges on its surface that could enhance the mass transfer rate of the negatively charged PYO based on the electrostatic attraction force.…”
Section: Nscps For Different Biosensor Applicationsmentioning
confidence: 96%
“…The commercially‐available Zensor TE100 SPE showed an excellent correlation between electrical signal loss and the viability of PA cells after antibiotic (colistin sulfate) exposure [ 73b,75 ] and to monitor the electrochemical response of PYO generated by bacteria in the presence of various amino acids ( Figure 8 A,B). [ 73b ] Maximal current peaks were reduced by ≈68% and 82% when exposed to colistin sulfate, a last‐resort treatment for cases of MDR PA infection.…”
Section: Electrochemical Detection Of Pamentioning
confidence: 99%
“…[ 73b ] Maximal current peaks were reduced by ≈68% and 82% when exposed to colistin sulfate, a last‐resort treatment for cases of MDR PA infection. [ 73b,75,76 ] Other EC studies for PYO‐tracing using SPEs as the primary tech include the commercially available SPE, Dropsens C223AT with a 1.6 mm Au WE, as well as Au CE and Ag RE. [ 64,74 ] Similarly to the Zenzor TE100, Dropsens C223AT SPEs are highly adaptable, having a low‐cost, high conductivity, and allow various electrochemical methods such as SWV, CV, DPV, thus being optimal for the electrochemical sensing of PYO.…”
Section: Electrochemical Detection Of Pamentioning
confidence: 99%